Protecting Cultural Heritage with High-Resolution Remote Sensing: A Study on the Ifugao Rice Terraces - Guo, Shuhao (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper explores the protection of cultural heritage using high-resolution remote sensing technology, with the Ifugao Rice Terraces in the Philippines as the study object. By comparing hyperspectral images from different periods, the changes in vegetation cover and soil erosion of the terraces are analyzed, the health status and soil characteristics of the terraces are assessed, and the main factors influencing environmental changes are identified. The results show that the ecological protection efforts for the Ifugao Rice Terraces have achieved some success, but some areas still require attention and timely ecological restoration. The study also integrates Geographic Information System (GIS) technology for comprehensive analysis to enhance the precision and efficiency of protection measures. This paper provides scientific evidence for understanding the spatial distribution and ecological environment of the terraces and offers valuable references for the protection and management of similar terrace areas, demonstrating the important role of high-resolution remote sensing technology in cultural heritage preservation.